FAW-Volkswagen Audi : pioneering the future (2012-present) - McFarlan, F. Warren (Franklin Warren); Jiao, Jie; Cao, Shanshan; Ma, Zijun; Yu, Yuanyuan (London : Tsinghua University School of Economics and Management, 2016)
The FAW-Volkswagen Audi "trilogy" case describes Audi's development history in China and the problems it faces currently, as well as demonstrating the strategies employed by FAW-Volkswagen Audi in their thirty year business partnership. The third case in the series describes how FAW-Volkswagen Audi responded to the decrease in the demand for luxury cars as the market matured and became stable.
Originally Published InMcFarlan, F. W., Jiao, J., Cao, S., Ma, Z., & Yu, Y. (2016). FAW-Volkswagen Audi: Pioneering the future (2012--present). Beijing: Tsinghua SEM China Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Volkswagenwerk; Audi AG; Automobile industry and trade -- China; Industrial efficiency; Factory management